Succession characteristics of phytoplankton functional groups and ecological assessment in a cold spring-type urban lake, China - Shen, Henglun; Xu, He; Zhang, Xinru; Zhu, Tianshun; Jiang, Wanxiang; Li, Xin (Frontiers in Microbiology, 2024)
Phytoplankton functional groups have been increasingly utilized in elucidating and predicting the response of phytoplankton species to environmental conditions and seasonal succession in various aquatic systems including lakes, rivers and reservoirs. However, it is still unclear whether the trait-based functional classification can be applied to spring-type lakes. To understand the temporal and spatial characteristics of phytoplankton functional groups and their responses to environmental factors in spring-type urban lake in northern China, an investigation was conducted in Daming Lake from May 2020 to September 2021. The findings revealed the identification of 98 phytoplankton taxa belonging to 6 phyla, predominantly being Chlorophyta (39.8%), Bacillariophyta (35.7%) and Cyanophyta (15.3%). The dominant species were Microcystis sp., Merismopedia minima, Synedra acus and Scenedesmus quadricauda. These phytoplankton taxa were categorized into 21 functional groups, with 6 dominant functional groups (abbreviated as D, MP, P, J, Lo, and W1). Among them, the functional group D, primarily constituted by S. acus, exhibited absolute predominance. The seasonal succession sequence of the dominant functional groups was as follows: D/P/J/MP/ Lo →→ D/P/W1/MP/Lo/J → D/P/J → D/MP → D/P/MP. Throughout the investigation period, the trophic level index (TLI) ranged from 39.10 to 71.13, and the Q index was from 1.91 to 2.91, both indicating a medium health state for Daming Lake, which was consistent with the evaluation results of the diversity index. The results of redundancy analysis revealed that the main driving factors of phytoplankton FG biomass and composition were water temperature (WT), total nitrogen (TN), transparency (SD), TN:TP (N:P), redox potential (ORP), chemical oxygen demand (CODMn) and pH. The dominance of the functional group D positively correlated with water temperature, TN, CODMn, pH and N:P but negatively correlated with SD. It was observed that functional groups and the Q index can objectively indicate the seasonal succession of phytoplankton and the water quality status of Daming Lake. Our discoveries have significant implications for the comprehension of the effects of urbanization on phytoplankton dynamics and for enhancing lake management practices to foster sustainable urban development.